2020
DOI: 10.1261/rna.077347.120
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial misreading in skeletal muscle accelerates metabolic aging and confers lipid accumulation and increased inflammation

Abstract: We have recently reported on an experimental model of mitochondrial mistranslation 2 conferred by amino acid exchange V338Y in the mitochondrial ribosomal protein MrpS5. 3 Here we used a combination of RNA-Seq and metabolic profiling of homozygous transgenic 3 MrpS5 V338Y/V338Y mice to analyze the changes associated with the V338Y mutation in post-3 mitotic skeletal muscle. Metabolic profiling demonstrated age-dependent metabolic changes 3 in the mutant V338Y animals, which included enhanced levels of age-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…With interest, we note that skeletal muscle and brain, sampled in parallel from the identical cohorts of MRPS5 V338Y/V338Y mutant mice, despite sharing the characteristic of postmitotic tissue, show disparate responses to impaired function of the 13 mtDNA encoded OXPHOS proteins. While for both tissues the effect of the MRPS5 V338Y mutation is age-dependent, we find bypassing of ETC by increased glycolysis, pentose phosphate pathway, fatty acid synthesis, and generation of lipid droplets in muscle [22], compared to increased flow through TCA and ETC in brain. Presumably, the latter reflects the dependency of neuronal cells on energy production via glycolysis feeding into TCA and ATP generation by oxidative phosphorylation.…”
Section: Discussioncontrasting
confidence: 55%
“…With interest, we note that skeletal muscle and brain, sampled in parallel from the identical cohorts of MRPS5 V338Y/V338Y mutant mice, despite sharing the characteristic of postmitotic tissue, show disparate responses to impaired function of the 13 mtDNA encoded OXPHOS proteins. While for both tissues the effect of the MRPS5 V338Y mutation is age-dependent, we find bypassing of ETC by increased glycolysis, pentose phosphate pathway, fatty acid synthesis, and generation of lipid droplets in muscle [22], compared to increased flow through TCA and ETC in brain. Presumably, the latter reflects the dependency of neuronal cells on energy production via glycolysis feeding into TCA and ATP generation by oxidative phosphorylation.…”
Section: Discussioncontrasting
confidence: 55%
“…In the context of aging, CPT1 expression in aged mice was shown to partially reverse aging-associated sarcopenia and fiber transition with increased muscle capillaries [ 106 ]. Shcherbakov et al further demonstrated the importance of mitochondrial integrity in muscle aging [ 107 ]. They used a genetically altered mitochondrial mistranslation experimental model, which presented impaired mitochondrial function in muscle.…”
Section: Evidence Linking Lipid Metabolism To Agingmentioning
confidence: 99%
“…They used a genetically altered mitochondrial mistranslation experimental model, which presented impaired mitochondrial function in muscle. Among the changes detected by RNA-sequencing and metabolomics analysis, they found that lipid metabolism and inflammation were increased in their model [ 107 ]. Those authors concluded that mitochondrial misreading in skeletal muscle accelerates metabolic aging, leading to lipid accumulation and increased inflammation, suggesting an important role for mitochondria and lipid metabolism in muscle aging.…”
Section: Evidence Linking Lipid Metabolism To Agingmentioning
confidence: 99%
“…6). To further control for aging-related transcriptomic changes in the control cohort, we projected the muscle transcriptome of the 9 and 15 months old wild-type animals on a previous between-group analysis (BGA) of 3 and 19 months old wild-type animals of the same C57BL/6 genetic background from another study 27 . In an age-dependent manner, the transcriptome of the 9 and 15 months old mice fell within the age boundaries defined by the 3 and 19 months old animals (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For age-related changes, C57BL/6 wild-type 9 and 15 months groups were compared to C57BL/6 wild-type mice of 3 and 19 months from another study of ours 27 . The gene expression in these four groups was compared by BGA 62 using the made4 package (bioconductor.org) in R. First, expression data from each study were batch corrected using ComBat from the sva package (version 3.32.1) in R. To remove noise and focus on those genes which change with age, the 7500 genes with the largest difference in expression between the 3 and 19 months groups were compared between all four groups.…”
Section: Methodsmentioning
confidence: 99%